2018
DOI: 10.1590/rbz4720170165
|View full text |Cite
|
Sign up to set email alerts
|

Use of a mixture of vegetal (Jatropha curcas) and animal (fish silage) byproducts as protein source in shrimp (Litopenaeus vannamei) diets

Abstract: This study evaluated growth responses of white shrimp Litopenaeus vannamei by testing different combinations of Jatropha curcas kernel meal (JCK) and tilapia waste silage (FS) as dietary protein sources under laboratory and pond conditions. A reference diet (RD) based on fish meal was elaborated to contain 35% crude protein and 434 kcal/g; then, five isoproteic and isoenergetic experimental diets were formulated from RD with different FS/JCK proportions as follows: 75%FS/0%JCK; 56.25%FS/13.25%JCK; 26.5%FS/30.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Many researchers also focused on the effects of dietary FS in shrimp. Rodríguez-González et al (2018) found that a combination of 18.75% FS/39.75% Jatropha curcas kernel meals in shrimp diets made better growth performance. And in a biofloc system, up to 6% of tilapia silage inclusion did not compromise shrimp meat quality (Gonçalves et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many researchers also focused on the effects of dietary FS in shrimp. Rodríguez-González et al (2018) found that a combination of 18.75% FS/39.75% Jatropha curcas kernel meals in shrimp diets made better growth performance. And in a biofloc system, up to 6% of tilapia silage inclusion did not compromise shrimp meat quality (Gonçalves et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…And FS has been successfully used as a substitute of fishmeal in several fish species (Liang et al, 2006;Goosen et al, 2016). Recently, more and more studies were conducted to evaluate the effect of dietary FS in shrimp at different nutrient combination conditions (Gallardo et al, 2012;Rodríguez-González et al, 2018) and biofloc system (Gonçalves et al, 2019;Lobato et al, 2019). Here, we examined the performances of replacement of fishmeal in L. vannamei diet with FS.…”
Section: Introductionmentioning
confidence: 99%